LINKAGES BETWEEN CORAL REEF CONDITIONS WITH THE DISTRIBUTION AND DIVERSITY OF MEGABENTHIC FAUNA IN THE WATERS OF BARRANGLOMPO ISLAND, MAKASSAR CITY - Syahrul, Muh.; Rani, Chair; Amri, Khairul (Hasanuddin University, 2022)
Coral reefs are the most diverse and complex underwater ecosystems in terms of biodiversity, including megabenthic fauna. Megabenthos is organism with a size of more than 1 cm that lives on the bottom/substrate of waters which includes attached, crawling and burrowing biota on the seabed. The research was conducted using the Line Intercept Transect and Benthos Belt Transect methods. The results of the study of coral conditions showed the percentage of live coral cover with conditions from bad to very good. The bad category was found in the west (24.56%) and south of the island (20.55%). The moderate category was found in the northwest (45.35%) and southwest of the island (30.08%) while the very good category was found in the north (80.68%) and south of the island (75.92%). The megabenthos found at the study site were 26 species from 10 megabenthos classes with densities in each category of coral conditions ranging from 12.11 to 23.51 individual/m². The highest density was found in moderate coral conditions dominated by Polycarpa aurata species and the lowest in very good coral conditions with the highest number of species found in poor coral conditions with 21 species and the lowest in very good conditions with 11 species. The species diversity (H') of megabenthos at the study site is in the low category. The high number of megabenthic species was associated with high dead coral and algae cover while high megabenthic density was associated with high other and abiotic cover in the form of sand substrate.